Neuromodulation and neuroprotective effects of chlorogenic acids in excitatory synapses of mouse hippocampal slices - Mara Yone D. Fernandes (Nature Portfolio, 2021)
Abstract The increased healthspan afforded by coffee intake provides novel opportunities to identify new therapeutic strategies. Caffeine has been proposed to afford benefits through adenosine A2A receptors, which can control synaptic dysfunction underlying some brain disease. However, decaffeinated coffee and other main components of coffee such as chlorogenic acids, also attenuate brain dysfunction, although it is unknown if they control synaptic function. We now used electrophysiological recordings in mouse hippocampal slices to test if realistic concentrations of chlorogenic acids directly affect synaptic transmission and plasticity. 3-(3,4-dihydroxycinnamoyl)quinic acid (CA, 1–10 μM) and 5-O-(trans-3,4-dihydroxycinnamoyl)-D-quinic acid (NCA, 1–10 μM) were devoid of effect on synaptic transmission, paired-pulse facilitation or long-term potentiation (LTP) and long-term depression (LTD) in Schaffer collaterals-CA1 pyramidal synapses. However, CA and NCA increased the recovery of synaptic transmission upon re-oxygenation following 7 min of oxygen/glucose deprivation, an in vitro ischemia model. Also, CA and NCA attenuated the shift of LTD into LTP observed in hippocampal slices from animals with hippocampal-dependent memory deterioration after exposure to β-amyloid 1–42 (2 nmol, icv), in the context of Alzheimer’s disease. These findings show that chlorogenic acids do not directly affect synaptic transmission and plasticity but can indirectly affect other cellular targets to correct synaptic dysfunction. Unraveling the molecular mechanisms of action of chlorogenic acids will allow the design of hitherto unrecognized novel neuroprotective strategies.